ASSESSMENT OF GREENING IN THE CONTEXT OF PROVIDING ENVIRONMENTAL PUBLIC GOODS IN AGRICULTURE (Polityki Europejskie, Finanse i Marketing)
The article discusses the concept of providing environmental public goods through agriculture. The theoretical goal of the discussion was to present the concept of greening under the EU's Common Agricultural Policy. This concept was developed on the basis of available literature and from EU and Polish documents. The concrete goal is to assess greening instruments in terms of their implementation and compliance by farmers. A review of the available literature on the subject allows the assumption that the greening instrument implemented under the CAP has contributed to an intensification of activities by farmers in the field of environmental protection. The article was prepared based on source materials, monographs and scientific articles as well as Eurostat data. The article also presents the results of Eurobarometer surveys that show the expectations of EU citizens towards the European Union's CAP in the field of environmental and climate protection. Results of surveys have shown that on the one hand, the European Union should be responsible for ensuring healthy and safe food products for consumers, while on the other hand the goal of the Common Agricultural Policy should be to ensure an appropriate standard of living for farmers.